CURRY-HOWARD CORRESPONDENCE - Tan, Xiao. (Tufts University. Tisch Library., 2021)
Thesis (M.S.)--Tufts University, 2021.; Submitted to the Dept. of Mathematics.; Advisor: David Smyth.; Committee: Loring Tu, and George McNinch.; Keywords: Logic, and Mathematics.